Investigating the Value of Urine Volume, Creatinine, and Cystatin C for Urinary Biomarkers Normalization for Drug Development Studies. (January 2019) - Adedeji, Adeyemi O.; Pourmohamad, Tony; Chen, Yafei; Burkey, Jennifer; Betts, Catherine J.; Bickerton, Susan J.; Sonee, Manisha; McDuffie, James E.
Novel urinary protein biomarkers have recently been identified and qualified in rats for the early detection of renal injury in drug development studies. However, there seems to be no standardized normalization method for analyzing these urinary biomarkers, as some users normalize with urinary creatinine (uCr), urine volume (uVol), or leave biomarker un-normalized. More recently, urinary cystatin C is also emerging as a urinary biomarker normalizer, given some of its characteristics as a glomerular filtration marker. The purpose of this study was to identify an optimal drug-induced kidney injury biomarker normalization method that can be adopted more uniformly in the field. To this end, we compared the variability of uVol, urinary cystatin C, and Cr in healthy rats; we evaluated the sensitivity of the renal biomarkers to renal injury after normalization with uVol, uCr, and cystatin C in rats with cisplatin-induced renal injury. We showed that, over time, uCr was less variable than urinary cystatin C and uVol. When the renal biomarkers were normalized with the 3 normalizing end points, the biomarkers showed (1) least variability following normalization with Cr in healthy animals and (2) poor sensitivity when normalized with urinary cystatin C in animals with renal injury. Overall, the results suggested that uCr is better than urinary cystatin C and uVol for normalizing renal biomarkers in rats under controlled preclinical conditions. To our knowledge, this is the first report that compared the variability of uVol, cystatin C, and Cr in the context of renal biomarkers' normalization.